Global Pathways: Contrasts and Convergences in Higher Education Internationalization - Amirudin, Jafar; Ijudin; Masripah (Yayasan Sinergi Kawula Muda, 2025)
The internationalization of higher education has become a critical strategy for enhancing institutional competitiveness, academic mobility, and global engagement. This study aims to compare approaches between developed and developing countries, examining key strategies, systemic barriers, and implications for global education equity. A narrative literature review was conducted using sources from Scopus, Google Scholar, and Web of Science, applying systematic inclusion and exclusion criteria. Keywords such as